The deep pectoral muscle flap in the cat: its vascular supply and potential use - Baines, S. J.; Gardner, J.; Allnutt, R.; White, R. A. S. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The vascular anatomy of the deep pectoral muscle in the cat was defined by contrast radiography of twelve deep pectoral muscles from six feline cadavers. The deep pectoral, muscle in the cat was found to have a type V vascular pattern with a dominant pedicle based on the lateral thoracic artery, with a contribution from the external thoracic artery, and secondary segmental pedicles arising from the internal thoracic artery, with numerous anastomoses between these two vascular fields. Following division of the sternal origin and elevation of the muscle flap, perfusion of the entire muscle from the dominant pedicle was identified. Transposition of the muscle flap within a wide arc of rotation was possible to include the chest wall, sternum, axilla and medial forelimb. This study demonstrates the potential suitability of the deep pectoral muscle flap for use in reconstructive surgery.The feline deep pectoral muscle has a type V vascular pattern, with a dominant pedicle based on the lateral thoracic artery, with a contribution from the external thoracic artery, and secondary segmental pedicles arising from the internal thoracic artery A clinically useful flap, supplied by the dominant pedicle, may be developed by incising the sternal origin of the muscle.
Keywords: Deep pectoral muscle; muscle flap; lateral thoracic artery; perfusion